Ferroptosis and central nervous system demyelinating diseases - Qin, Danqing; Li, Dong; Wang, Chunjuan; Guo, Shougang (Journal of neurochemistry, 2023)
Ferroptosis is a newly discovered programmed cell death caused by intracellular iron excess and glutathione (GSH) system imbalance, resulting in fatal lipid peroxidation. It is different from necrosis, apoptosis, autophagy, and other forms of cell death. Accumulating evidences suggest that brain iron overload is involved in the pathogenesis of demyelinating diseases of the central nervous system (CNS), such as multiple sclerosis (MS), neuromyelitis optica (NMO), and acute disseminated encephalomyelitis (ADEM). The study of ferroptosis may provide a new understanding of demyelinating diseases and provide a novel therapeutic target for clinical treatment. Herein, we reviewed recent discoveries on mechanisms of ferroptosis, the effects of metabolic pathways on ferroptosis, and its involvement in CNS demyelinating diseases. Ferroptosis is the result of multiple biological pathways acting together as a newly discovered cell death program. The major metabolic pathways associated with ferroptosis susceptibility include iron metabolism, lipid metabolism, and amino acid metabolism. Ferroptosis plays a key role in the pathophysiology of central nervous system (CNS) demyelinating diseases. Blocking the process of iron death can reduce myelin damage and alleviate the neurological dysfunction caused by demyelinating diseases such as multiple sclerosis, neuromyelitis optica, and acute disseminated encephalomyelitis.